Evidence-Based Librarianship Down Under: Improving a Nation’s Resource-Sharing - Çev.: Güler Demir (Türk Kütüphaneciliği)
This study is a translation of the "Evidence-based librarianship Down Under: improving a nation's resource-sharing" section in the book headed "Evidence-based Librarianship: Case Studies and Active Learning Exercises." Roxanne Missingham, the author of the section in question, is a librarian with a work experience in the Australian Parliament and the National Library, who also has the responsibilities of the vice-presidency of the Australian Library and Information Association at the same time. In general, the book emphasizes the knowledge and evidence gained in the development of library services as a result of a combination of usercollected data, librarians' experiences, scientific, professional research and observations, and active learning practices that encourage critical thinking through case-based case studies. The purpose of the specifically translated section is to present an assessment of the development of countrywide resource sharing through a national benchmarking study in Australia on the subject and an evaluation of the impact from an evidence-based librarianship approach using a survey and data from libraries in 2006. It is hoped that it will both shed light on the application field of similar works and provide a contribution to the Turkish literature.